Land Tenure Security and Health Nexus: A Conceptual Framework for Navigating the Connections between Land Tenure Security and Health - Walter Dachaga; Walter Timo de Vries (Land, 2021)
The rise of urban populations has rendered cities in both developed and developing countries vulnerable to poor health and diseases that are associated with urban living conditions and environments. Therefore, there is a growing consensus that while personal factors are critical in determining health, the urban environment exacerbates or mitigates health outcomes, and as such the solution for improving health outcomes in urban settings can be found in addressing socio-environmental factors that shape urban environments. Land tenure security is a social environmental factor of health that has been understudied by urban geographers despite its obvious role in shaping urban environments, housing conditions, and health. We interpret literature and infer possible pathways through which land tenure security connects to health and propose a land tenure security and health nexus conceptual framework for modeling and investigating the extent of this connection. Based on a narrative review of literature, this inter-disciplinary paper shows that land tenure security can influence health outcomes via four pathways—infrastructure access, environmental justice, psycho-ontological security, and social cohesion. Going forward, a subsequent investigation can focus on developing an index of land tenure security health insults, based on which an empirical investigation of the relationship between land tenure security and health disease is possible.